EPCO-24. MULTI-OMIC PROFILING OF PATIENT-DERIVED SUBCLONES IDENTIFIES AGGRESSIVE CELLULAR SUBPOPULATIONS IN PAEDIATRIC DIFFUSE HIGH GRADE GLIOMAS (PDHGGS). (14th November 2022) - Kessler, Ketty; Grabovska, Yura; Burford, Anna; Temelso, Sara; Tari, Haider; Molinari, Valeria; Crampsie, Shauna; Yu, Lu; Choudhary, Jyoti; Proszek, Paula; Hubank, Mike; Mackay, Alan; et al.
Abstract: Paediatric-type diffuse high-grade gliomas are classified into distinct subgroups based upon their location and defining molecular alterations, with very poor clinical outcomes in patients >3yrs. This extensive inter-tumour heterogeneity is further complicated by a wide diversity of genotypically- and phenotypically-distinct subclonal populations within individual tumours, providing a substantial barrier to developing effective treatments. We aimed to understand the dynamic cellular make-up of PDHGGs such that novel strategies aimed at targeting specific subpopulations based upon their contribution to disease progression as whole may be employed. Two complementary approaches have been undertaken to address this – first by carrying out single-cell profiling of bulk specimens, and the second isolation and propagation of single-cell-derived stem cell-like cultures in vitro. To-date we have studied 10 cases and a total of 218 subclonal colonies from both DMG-H3K27 and DHG-WT. In a spinal metastatic case of DMG-H3K27, lpWGS/FISH highlighted subpopulations driven by mis-segregation of amplified oncogenic ecDNA, and mutually exclusive subpopulations defined by MYCN, PDGFRA and CCND1. Through integrated analysis of scRNA-seq and scATAC-seq, we show distinct chromatin accessibility profiles to underlie gene expression signatures defining unique subpopulations of cells. In addition to cycling populations and those associated with lineage-specificity, we identified 'aggressive' subpopulations defined by significant upregulation of immediate early response genes such as FOS/FOSL1/JUN, those associated with promotion of invasion/migration such as SERPINs and MMPs. These subpopulations could be mapped to isolated single-cell-derived subclones with highly proliferative and/or motile phenotypes, defined by comprehensive profiling of expressed and secreted proteins. Differential cis-regulation driving cell identity/tumorigenesis was found in one example to occur via a trans-histone mechanism mediated by an H4-lysine-methyltransferase, KMT5B. Application of functionally-defined interventional strategies aimed at disrupting the interactions between these subpopulations based upon evolutionary biology principles may offer a novel approach to treat these otherwise incurable tumours in children and young adults.